2015
DOI: 10.1093/ve/vev008
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental evolution of an RNA virus in cells with innate immunity defects

Abstract: Experimental evolution studies have shown that RNA viruses respond rapidly to directional selection and thus can adapt efficiently to changes in host cell tropism, antiviral drugs, or other imposed selective pressures. However, the evolution of RNA viruses under relaxed selection has been less extensively explored. Here, we evolved vesicular stomatitis virus in mouse embryonic fibroblasts knocked-out for PKR, a protein with a central role in antiviral innate immunity. Vesicular stomatitis virus adapted to PKR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…This makes it difficult to identify adaptive mutations by looking at parallel evolution events. Previous work with VSV has revealed greater levels of parallel sequence evolution than those observed here in some cases, but not in others ( Cuevas, Elena, and Moya 2002 ; Novella et al 2004 ; Remold, Rambaut, and Turner 2008 ; Cuevas, Moya, and Sanjuán 2009 ; Garijo et al 2014 , 2016 ; Hernández-Alonso et al 2015 ). The reasons for these differences might be attributed to effective population sizes (determined mainly by inoculum sizes), evolutionary time (number of transfers), and the strength of the selective pressures applied, among other possible factors ( Sanjuán and Grdzelishvili 2015 ).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…This makes it difficult to identify adaptive mutations by looking at parallel evolution events. Previous work with VSV has revealed greater levels of parallel sequence evolution than those observed here in some cases, but not in others ( Cuevas, Elena, and Moya 2002 ; Novella et al 2004 ; Remold, Rambaut, and Turner 2008 ; Cuevas, Moya, and Sanjuán 2009 ; Garijo et al 2014 , 2016 ; Hernández-Alonso et al 2015 ). The reasons for these differences might be attributed to effective population sizes (determined mainly by inoculum sizes), evolutionary time (number of transfers), and the strength of the selective pressures applied, among other possible factors ( Sanjuán and Grdzelishvili 2015 ).…”
Section: Discussioncontrasting
confidence: 65%
“…Although evolutionary repeatability was relatively low, some interesting parallel evolution events can be identified by comparing across studies. First, the E254K substitution in gene G, which appeared in line E1, was previously reported in 4/5 WT lines evolved in MEFs ( Hernández-Alonso et al 2015 ). Interestingly, this mutation was shown to be deleterious when assayed individually by site-directed mutagenesis, suggesting epistasis with other mutations.…”
Section: Discussionmentioning
confidence: 79%
“…It is possible that differences in the immune status of mice from each group result in different selective pressures on the virus population. Several studies have shown that the innate immune system is involved in viral evolution [59,60]. Finally, obese mice are expected to have more adipocytes (i.e., fat cells) while undernourished mice are expected to have fewer.…”
Section: Discussionmentioning
confidence: 99%
“…Directed evolution and bioselection for more potent oncolytic viruses has been explored in other studies using a variety of oncolytic viruses and cancer types (50)(51)(52)(53)(54)(55)(56). VSV has been a widely used model to study viral evolution for several decades (57) and has been experimentally evolved for various purposes, such as understanding how viruses evade innate immune responses (58) and the generation of novel VSV-G protein variants used to pseudotype retroviral and lentiviral vectors for gene delivery (59) and to produce novel variants of foreign proteins encoded in VSV genome (60). Moreover, several previous studies have successfully used a directed evolution approach to improve VSV's oncolytic abilities (61)(62)(63)(64).…”
mentioning
confidence: 99%